The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.ppat.1007716
|View full text |Cite
|
Sign up to set email alerts
|

Potent neutralizing antibodies elicited by dengue vaccine in rhesus macaque target diverse epitopes

Abstract: There is still no safe and effective vaccine against dengue virus infection. Epidemics of dengue virus infection are increasingly a threat to human health around the world. Antibodies generated in response to dengue infection have been shown to impact disease development and effectiveness of dengue vaccine. In this study, we investigated monoclonal antibody responses to an experimental dengue vaccine in rhesus macaques. Variable regions of both heavy chain (VH) and light chain (VL) were cloned from single anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…The higher levels of IgG and neutralizing antibody (FRNT 50 ) titers elicited in the murine model after immunization with PSNPs conjugated with the multi-epitope DENV peptide vaccine containing B1 derived from the E protein showed that it was more effective when compared to B2, which was derived from the NS4A protein. This observation supported the conclusion from previous studies stating that neutralizing antibodies were largely elicited by the E protein [ 41 , 42 ]. Li et al (2011) evaluated a B cell epitope from the domain III (DIII) of the E protein of DENV2 [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…The higher levels of IgG and neutralizing antibody (FRNT 50 ) titers elicited in the murine model after immunization with PSNPs conjugated with the multi-epitope DENV peptide vaccine containing B1 derived from the E protein showed that it was more effective when compared to B2, which was derived from the NS4A protein. This observation supported the conclusion from previous studies stating that neutralizing antibodies were largely elicited by the E protein [ 41 , 42 ]. Li et al (2011) evaluated a B cell epitope from the domain III (DIII) of the E protein of DENV2 [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have identified that adjacent to the fusion loop, another similar loop exists in most of the flaviviral (e.g. WNV, TBE, JEV, YFV) envelope (Fibriansah and Lok, 2016;Li et al 2019). Our previous bioinformatics studies have also shown that the envelope of all DENV serotype consists of four conserved regions (> 90%), and two of them were found in domain II, in which one is fusion loop (Fu) with more than 99% conservation and another is its nearby bc loop (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although, recombinant EDIII domain injected by plasmid DNA or purified from bacterial expression systems was found to be poorly immunogenic, and has shown low protective efficacy in animal model (Guzman et al 2010). On the other hand, EDII has been reported as the dimerisation domain and consists of the most conserved fusion (Fu) and bc loop (Li et al 2019;Zhang et al 2004). Several studies have also shown that the conserved Fu loop is highly immunogenic (Lai et al 2008;Cherrier et al 2009;Smith et al 2013), and induces cross-reactive antibodies, of which some are crosstalk with adjacent bc loop (Gallichotte et al, 2015;Cherrier et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The heavy chain and light chain variable region sequences of gB antibody LJP538 [ 25 ] were obtained from a published patent (PCT/IB2015/057664) and cloned into human IgG1 backbone for expression. A dengue virus specific human IgG1 antibody [ 61 ] was used as isotype control. The 3–25 Fab was generated by digesting 3–25 IgG with papain (Sigma, P4762) as described previously [ 62 ].…”
Section: Methodsmentioning
confidence: 99%